Neutrophil/lymphocyte ratio and mean platelet volume in branch retinal vein occlusion - Turkseven Kumral, Esra (Saudi J Ophthalmol, 2016)
PURPOSE: To evaluate the mean platelet volume (MPV) and the neutrophil/lymphocyte ratio (NLR) in patients with branch retinal vein occlusion (BRVO). METHODS: Thirty patients with branch retinal vein occlusion (BRVO group) and 27 age and sex matched subjects (control group) were included in the study. MPV and NLR parameters obtained from peripheral blood were recorded. RESULTS: The mean age was 62.6 ± 12.3 years in BRVO and 63.5 ± 8.2 years in control group. The BRVO group consisted of 13 males and 17 females and the control group included 12 male and 15 female subjects. The mean MPV values were 8.64 ± 2.01 fL in BRVO group and 8.5 ± 1.26 fL in control group. NLR was 2.24 ± 0.79 and 1.89 ± 0.64 in BRVO and control groups respectively. The difference between two groups in terms of MPV and NLR was not statistically significant. CONCLUSION: MPV and NLR were found to be not affected in branch retinal vein occlusion patients.